Immunotherapy using anti-PD-1 and anti-PD-L1 in Leishmania amazonensis-infected BALB/c mice reduce parasite load - da Fonseca-Martins, Alessandra M. (Sci Rep, 2019)
Leishmaniasis is a neglected disease, for which current treatment presents numerous issues. Leishmania amazonensis is the etiological agent of cutaneous and diffuse cutaneous leishmaniasis. The roles of the programmed death-1 (PD-1) receptor on lymphocytes and its ligand (PD-L1) on antigen-presenting cells have been well studied in tumor and other infection models; but little is known about their roles in non-healing cutaneous leishmaniasis. In this study, we observed that L. amazonensis induced PD-1 expression on both CD4(+) and CD8(+) T cells and PD-L1 on dendritic cells on BALB/c mice. We tested the therapeutic potential of anti-PD-1 and anti-PD-L1 monoclonal antibodies (MoAbs) against a non-healing L. amazonensis infection in BALB/c mice, and that anti-PD-1 and anti-PD-L1 treatment significantly increased IFN-γ-producing CD4(+) and CD8(+) T cells, respectively. Compared with infection controls, mice treated with anti-PD-1 and anti-PD-L1, but not anti-PD-L2, displayed bigger lesions with significantly lower parasite loads. Treatment did not affect anti-Leishmania antibody (IgM, IgG, IgG1 and IgG2a) or IL-10 production, but anti-PD-1 treatment reduced both IL-4 and TGF-β production. Together, our results highlight the therapeutic potential of an anti-PD-1-based treatment in promoting the reinvigoration of T cells for the control of parasite burden.